Atherosclerosis treatment with nanoagent: potential targets, stimulus signals and drug delivery mechanisms - Luo, Ting; Zhang, Zhen; Xu, Junbo; Liu, Hanxiong; Cai, Lin; Huang, Gang; Wang, Chunbin; Chen, Yingzhong; Xia, Long; Ding, Xunshi; Wang, Jin; Li, Xin (Frontiers in Bioengineering and Biotechnology, 2023)
Cardiovascular disease (CVDs) is the first killer of human health, and it caused up at least 31% of global deaths. Atherosclerosis is one of the main reasons caused CVDs. Oral drug therapy with statins and other lipid-regulating drugs is the conventional treatment strategies for atherosclerosis. However, conventional therapeutic strategies are constrained by low drug utilization and non-target organ injury problems. Micro-nano materials, including particles, liposomes, micelles and bubbles, have been developed as the revolutionized tools for CVDs detection and drug delivery, specifically atherosclerotic targeting treatment. Furthermore, the micro-nano materials also could be designed to intelligently and responsive targeting drug delivering, and then become a promising tool to achieve atherosclerosis precision treatment. This work reviewed the advances in atherosclerosis nanotherapy, including the materials carriers, target sites, responsive model and treatment results. These nano-agents precisely delivery the therapeutic agents to the target atherosclerosis sites, and intelligent and precise release of drugs, which could minimize the potential adverse effects and be more effective in atherosclerosis lesion.